Development of Augmented Reality-Based Learning Media Using Assemblr EDU Integrated with Contextual Teaching and Learning (CTL) for the Human Respiratory System - Cahaya Dewi Ratih; Subuh Anggoro; Masanori Fukui (Postgraduate, University of Mataram, 2025)
The concept of the human respiratory system is abstract, making it difficult for elementary school students in the concrete operational thinking stage. Schools primarily use textbooks and conventional teaching aids, which lack interactive visual support. A questionnaire administered to 54 students revealed that 81.84% found it easier to understand the material with 3D visualization, and 90.74% were interested in learning using technology-based media. These findings highlight the need for contextual and visual learning media. This study aims to develop Augmented Reality-based learning media using the Contextual Teaching and Learnig (CTL) approach through the Assemblr EDU application; determine its feasibility through expert validation; analyze its practically through limited trials with students; and analyze teachers’ responses during the dissemination phase. The research employed a Research and Development method using the 4D model, which includes Define, Design, Develop, and Disseminate stages. Data collection techniques involved interviews, expert validation questionnaires, and student and teacher response questionnaires. Validation results indicated high feasibility, with scores of 88.57% (content expert) and 82.67% (media expert). Trials with 12 students showed a practicality score of 91.67% (very interesting) and teacher responses averaged 89.14% from 50 teachers. The developed media is feasible, practical, and potentially applicable in elementary science learning.